Type II diabetes in systemic sclerosis patients: insights from an observational, multicenter study of GIRRCS (Gruppo Italiano di Ricerca in Reumatologia Clinica e Sperimentale) - Vasiliki Liakouli; Giulio Forte; Piero Ruscitti; Luca Navarini; Francesca Bellisai; Francesco Caso; Giuliana Guggino; Lidia La Barbera; Chiara Rizzo; Ada Corrado; Paola Triggianese; Alberto Lo Gullo; et al. (Arthritis Research & Therapy)
Abstract Objective To assess the contribution of Systemic sclerosis (SSc)-specific features on type II diabetes mellitus (T2D) in a large cohort of Italian SSc patients. Methods A total of 613 SSc patients from 11 tertiary Rheumatology Units across Italy were included. All patients underwent full history taking, clinical examination, and relevant laboratory and radiological evaluations. Demographic, socioeconomic, and disease-specific factors were compared between SSc patients with and without T2D. Results The prevalence of T2D in the study cohort was 7.6%. SSc patients with T2D were significantly older (P < 0.007) and exhibited: higher prevalence of late-stage capillaroscopic pattern (P < 0.001), severe reduction in forced vital capacity (FVC < 50%; P < 0.000), moderate reduction in total lung capacity (TLC 50–69%; P < 0.011), electrocardiographic signs of right ventricular hypertrophy (P < 0.018), higher prevalence of pulmonary arterial hypertension (PAH) confirmed by right heart catheterization (RHC) (P < 0.037) and higher prevalence scleroderma renal crisis (SRC) (P < 0.001); elevated erythrocyte sedimentation rate (ESR) (P < 0.022), and ANA positivity. These patients more frequently assumed angiotensin-converting enzyme inhibitors (ACEi) (P < 0.005) when compared to their non-T2D counterparts, while the use of immunosuppressive therapies was similar between groups. Multivariate analysis identified older age, SRC, and reductions in both TLC and FVC as independent SSc-specific associated factors of T2D. Conclusion Although the prevalence of T2D in SSc patients is lower than the global estimates reported by the International Federation of Diabetes (IFD), a distinct subgroup of SSc patients with T2D is characterized by unique disease manifestations and complications, including SRC and impaired lung function. These findings underscore the importance of tailored screening and management approaches to address the intersecting metabolic and vascular risks in this population.